Design and Construction of an Automatic Chili Plants Watering System Based on the Internet of Things (IoT) Using the Blynk App - Aisyah, Siti; Nasution, Mulkan Iskandar; Nasution, Nazaruddin (Jurnal Pijar Mipa, 2024)
Chili is one of the vegetables cultivated by Indonesian farmers because of its high market value and many health benefits. Manual watering of plants still has weaknesses because water use is unlimited, especially for chili plants. Therefore, IoT is needed to water plants automatically and in real-time based on soil moisture and can monitor chilli plants' air temperature and pH. This research aims to replace manual watering with automatic watering. The system was tested and installed in a greenhouse using UV plastic measuring 70cm × 70cm × 70cm. The microcontroller used is ESP32. Other components are RTC DS3231, capacitive soil moisture sensor, DHT22 sensor, soil pH sensor, water pump, and blynk application. This device operates when reading input from the RTC, namely 07:00 WIB and 17:00 WIB. The watering pump will work at humidity <60% and stop at humidity >80%. At temperatures <24˚C, the lamp will be active and at temperatures >33˚C to <55˚C, condensation will be carried out using a nozzle sprayer. The soil pH sensor detects soil conditions, namely acidic, neutral or alkaline. The results of this research are quite good and follow the designed program. The average % error on the DHT22 sensor is 1.433%, and the soil pH sensor is 0.74%. Capacitive soil moisture sensors are also quite good at reading soil moisture conditions. Likewise, the RTC test has a time difference of only 6 seconds with the comparison tool.